Seismic Performance Evaluation of Asymmetric Reinforced Concrete Tunnel Form Buildings. (May 2017) - Beheshti Aval, Seyed Bahram; Asayesh, Mohammad Javad
Abstract: Despite the excellent seismic resistance characteristics of reinforced concrete tunnel form (RCTF) buildings, their predominant torsional vibration modes, especially those related to asymmetric RCTF constructions, make them vulnerable to strong seismic ground motions. For this reason, design guidelines prohibit the construction of multi-story RCTF buildings with asymmetric plans. This lack of relevant code provisions in turn, forces the engineer to apply design methods relevant to typical reinforced concrete (RC) buildings despite the well-known differences in the seismic performance when compared to RCTF buildings. This issue becomes more challenging when one is interested in asymmetric RCTF buildings whose past seismic performance is generally unknown. The present study investigates the seismic performance of two-, five-, and fifteen-story asymmetric RCTF buildings with two distinct plans. A number of parameters such as the percentage of walls at each story level and the in-plan eccentricity, on the lateral capacity of the building subjected to strong ground motions are highlighted. The effect of coupling beams (spandrels) on performance of RCTF constructions is also examined. It is concluded that they do not generally contribute in strength and ductility of low height constructions and in taller ones; due to inducing more demands, these low strength shear-failure-type members fail prematurely. However, if these elements are designed based on building code requirements and implemented with adequate shear reinforcements, they may be used as the structural fuses for dissipating seismic energy. The multilevel performance-based response modification factor (R-factor) is considered in order to capture the seismic performance of the RCTF structures. Relevant demand/supply R-factors are determined for this particular case study involving all the effective parameters such as ductility, over-strength, redundancy, seismic hazard level, and performance level. As a general conclusion, the results of the research show an excellent seismic performance of this type of structures in spite of their inherent irregularities. The high lateral stiffness and strength of the RCTF building compensates for the relatively low torsional stiffness with respect to lateral stiffness; as a result of which, the building exhibits superior seismic performance in high seismic hazard regions.